TEACHING DURING THE COVID-19 CRISIS AS REFLECTED AND SHARED ON FACEBOOK - Khoi, Mai Ngoc; Tuyet, Khac Thi Anh (VNU Journal of Foreign Studies, 2021)
As in many countries worldwide, the COVID-19 pandemic requires Vietnamese teachers to adapt to online teaching. A particular challenge has been the urgent and unexpected requests for the immediate shift from face-to-face to online teaching. This research focuses on how teachers at a university reacted and adapted to the change, as reflected and shared on their Facebook pages. 96 Facebook posts of 56 university lecturers during the online teaching phases in 2020 and early 2021 were screen-captured and then thematically analysed. Main factors causing difficulties and teacher stress and burnout were identified. The findings suggest that the toughest challenges were two aspects: the difficulties in controlling the dynamics and interactions in the class, and the difficulties in arranging workload in school curricula filled with online classes. The findings show that teachers' attitude toward this sudden change slowly improved as their efficacy for teaching online and sense of accomplishment increased. The paper also discusses the future changes relevant for sustainable online education. Finally, the paper ends with some reflection on helping teachers survive a crisis by nurturing a positive attitude and resilience.